Effect of pruning mother suckers on daughter sucker production in cardamom (Elettaria cardamomum M.) seedlings - KUMAR, M R SUDHARSHAN, SIDDAGANGAIAH SIDDAGANGAIAH, V KRISHNA (Journal of Spices and Aromatic Crops, 1993)
The effect of pruning mother suckers on daughter sucker production, growth and development of nursery seedlings of cardamom (Elettaria cardamomum) is reported. The number of suckers produced was significantly higher in seedlings pruned at 5 months of age followed by seedlings pruned at 3 months of age. The study indicated that pruning was not helpful in in creasing biomass and hence it may not be necessary to remove apical meristem (mother sucker pruning) before transplanting of nursery seedlings.